Natural Killer Cell Cytotoxicity Is Not Regulated by Folic Acid in Vitro - Montoya-Kunsting, M (2013)
Objectives: Folate supplementation may be associated with an increased risk of developing several types of cancer and a derangement of immune function. Among the latter, Natural killer (NK) cells are involved in non-MHC-restricted natural immunity against malignant target cells. Abnormalities in NK cell number or function have been associated with a higher cancer risk. The aim of this study was to study in vitro the possible effect of different concentrations of 5-methyltetrahydrofolic acid (5-MTHF) or folic acid on NK cell cytotoxic function, and expression of the stimulatory and inhibitory receptors KIRDL4, KIRDL3, and NKG2D. Methods: Volunteer-derived peripheral mononuclear cells (PBMC) and highly enriched NK cells (95% CD56+ CD16+) were grown in folic acid free-RPMI 1640, supplemented either with folic acid or 5-MTHF (15-100 nM) during 72 h to 96 h. Results: No differences in the cytolytic activity of PBMC and enriched NK cells were observed. After 96 h of in vitro culture without folate or supplemented with FA or 5-MTHF (30 or 100 nM), there were no changes in the percentage of HPNK receptor-positive cells. Conclusions: Our data indicate that a high dose of 5-MTHF or folic acid does not influence NK cell function in vitro. © 2013 Elsevier Inc.